Monoacylglycerol lipase inhibition as potential treatment for interstitial cystitis. (October 2019) - Chinnadurai, Anu; Berger, Geraint; Burkovskiy, Ian; Zhou, Juan; Cox, Ashley; Lynch, Mary; Lehmann, Christian
Abstract: Interstitial cystitis is a chronic inflammatory condition of the urinary bladder with an unclear etiology. Currently, there are no widely accepted long-term treatment options available for patients with IC, with the European Association of Urology (EAU, 2017 guidelines), American Urology Association (AUA, 2014 guidelines), and the Royal College of Obstetricians and Gynaecologists (RCOG, 2016 guidelines) all suggesting various different conservative, pharmacological, intravesical, and surgical interventions. The endocannabinoid system represents a potential target for IC treatment and management. Activation of cannabinoid receptor 2 (CBR2) with various agonists has previously been shown to reduce leukocyte differentiation and migration, in addition to inhibiting the release of pro-inflammatory cytokines at the site of inflammation. These receptors have been identified in the detrusor and sensory nerves of the urothelium in various mammalian species, including humans. We hypothesize that by inhibiting the enzymes responsible for the catabolism of endogenous cannabinoids locally, bladder concentrations of CBR2 agonists will increase, particularly 2-arachidonyl glycerol, resulting in a diminished inflammatory response.